Dry turning of tempered martensitic stainless tool steel using coated cermet and coated carbide tools. - Noordin, M. Y.; Venkatesh, V. C.; Sharif, Safian (Elsevier B.V., 2007)
Turning trials were performed under dry cutting conditions with constant depth of cut in order to investigate the usability of coated TiCN based cermet (KT 315) and coated carbide (KC 9110) cutting tools to turn tempered martensitic stainless tool steel with hardness in the 43-45 HRC range. Cutting speed, feed and the side cutting edge angle (SCEA) of the tool were the independent variables considered. Regardless of the cutting tool material, cutting speed and feed expectedly have an effect on tool wear and tool life. Additionally, the SCEA is found to influence the tool life where the tool life increases, as the SCEA was changed from 0° to -5°. The longest tool life was attainable when cutting with KT 315 at low cutting speed and feed rate when using -5° SCEA. However, in all other instances, KC 9110 outperforms KT 315. This is particularly evident at medium and high cutting speeds and feed. The constant and exponent for the various Taylor tool life equations have been determined. Flank wear, end clearance wear and catastrophic failure were the main types of tool failure mode determining tool life. The wear mechanisms for the various tool failure modes were suggested. The results suggest that dry turning of hardened, stainless tool steel could be performed using coated TiCN based cermet and coated carbide cutting tools with -5° SCEA at suitably selected cutting speed and feed combination.